Psikoedukasi Literasi Kesehatan Mental: Gangguan Psikologis Pada Mahasiswa - LAILATUL IZZAH; Silawati; Raspan Hamdi; Eva Yuliza; Sepna Fanny (LPPI UMN AL WASHLIYAH, 2024)
Lack of knowledge about Mental Health, Psychological Disorders, can lead to a lack of ability to identify specific mental health problems, the emergence of misconceptions and attitudes about mental health issues, and the lack of proper behavior when dancing abntuation. The dedication to the psychoeducational literacy theme Mental Health: Psychological Disorder aims to enable students to understand mental health issues: psychological disorders, have the right beliefs and perceptions about mental health problems: psychologic disorder, and change the way they seek help for mental health problem: psychical disorder. At UIN Suska Riau, our process consists of pre-tests, lectures on mental health (affective disorders), discussions and psychological consultations for students, and then post-test. Average pretest score of 1130 and an average posttest score of 1330 indicates that psycho-educational activities aimed at improving mental health literacy: Psychological disorders in students are achieved. An increase in the posttest value compared to the pretest value shows this.